(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND Neurological disturbances after open inguinal hernia repair affect approximately one in ten patients. Sutureless, self-gripping meshes were developed with the aim of reducing postoperative neurological disturbances or neuralgia. This study assessed short- and long-term outcomes after open inguinal hernia repair using a self-gripping light-weight mesh in a peripheral teaching hospital. METHODS Patients with uni- or bilateral inguinal hernia were included in this study. Open inguinal hernia repair was performed according to the Lichtenstein technique with a self-gripping, lightweight macroporous mesh. Postoperative follow-up was at 6 weeks after surgery and any long-term complications or recurrences were recorded up to 5 years postoperatively. RESULTS The median follow up time for all patients was 5–6 years and the median operation time was 40.0 minutes (inter quartile range 25.0–55.8). Of the 162 included patients, the mean numeric rating scale for pain (0 = no pain, 10 = excruciating pain) before hospital discharge was 2.7 (standard deviation [SD] 2.6) and 1.1 (SD 1.1) at 6 weeks postoperatively. The overall incidence of neurological disturbances at 6 weeks postoperatively was 11% when surgery was performed by the chief of surgery and 40% when it was performed by a senior consultant, 49% by chief-residents and 47% by supervised residents (p = 0.005). Patients with neurological disturbances were younger than asymptomatic patients (age 50, SD 15 vs 62, SD 17, p <0.001). The 1-, 3- and 5-year recurrence rates were 1%, 2% and 3%, respectively. CONCLUSIONS This study shows that open inguinal hernia repair using a self-gripping mesh is feasible, with a short operation time and low hernia recurrence rates in a peripheral teaching hospital. However, significant differences in neurological disturbances dependent on the surgeons experience were identified. Especially younger patients should be operated on by an experienced surgeon to reduce neurological disturbances and neuralgia.